On the comparison of extensive and intensive measures of the efficiency of scientific groups - Mryglod, O. I.; Kenna, R.; Holovatch, Yu. V.; Berche, B. (Reports of the National Academy of Sciences of Ukraine, 2014)
The problem of scientific efficiency evaluation is discussed. On the one hand, there is no simple but reliable way to assess the individual or collective scientific performance. It is a challenge to decide which approach, i. e. peer-review or citation-based indicators, should be used for this purpose. On the other hand, differences between the disciplines should be taken into account for the assessment. We analyze correlations between values of citation-based impact indicators and peer-review scores for British scientific groups in several academic disciplines, from natural to social sciences and humanities.